Segmentasi Paru-Paru pada Citra X-Ray Thorax Menggunakan Distance Regularized Levelset Evolution (DRLSE) - Hariyadi, M Amin (Department of Informatics Engineering, 2017)
– Lung is one in control in the circulatory system of air (oxygen) in the human body, so the detection of disorders of the human respiratory urgently needed to detect any disturbance in the lungs used X-ray beam, from the results of x-ray image of the thorax contained information used to analyze and determine the shape of an object from the lungs, in order to obtain such information, a process of segmentation. In this study used methods Distance regularized Levelset Evolution (DLRSE), this method region based models which is an improvement of edge-based models. The purpose of this study to implement segmentation methods DRLSE the lungs of the results of x-ray image of the thorax. The trial results with the system DLRSE method performed on the 20 data from X-ray image of the thorax obtained an average result accuracy of 87.90%, a sensitivity of 76.27% and a specificity of 93.98%.